The influence of occupational safety and health on employee performance through work discipline at pt united tractors site loa janan sanga - Putri Hendiani; Tuti Wediawati (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of occupational safety and health on employee performance through work discipline. The type of research used is explanatory research using a quantitative approach. The sample used was 40 respondents who were employees of the mechanic section of the Loa Janan Sanga site using a non-probability sample using the saturated sample technique. The data analysis used is path analysis. The results showed that the Occupational Safety variable had no significant effect on the Work Discipline variable, the Occupational Health variable had a positive and significant effect on the Work Discipline variable, the Work Discipline variable had a positive and significant effect on the Employee Performance variable, the Occupational Safety variable had no significant effect on the Employee Performance variable, the Occupational Health variable has no significant effect on the Employee Performance variable, the Work Safety variable through Work Discipline as an intervening variable has a significant effect on the Employee Performance variable and the Occupational Health variable through Work Discipline as an intervening variable has a significant effect on the Employee Performance variable. Thus, PT United Tractors Site Loa Janan Sanga continues to strive to implement the K3 program properly and supervise employees against the rules and regulations that apply in the Company. This will make employees safe and healthy and continue to maintain work discipline which will avoid the risk of work accidents and create good employee performance.